qanda-logo
search-icon
Símbolos
Problema
solution-image
$\left(6x+5\right)-\left(-3x+7\right)=$ $\left(6x+5y+8\right)-\left(3x+7y-6\right)=$ $\left(x-2y+32+5\right)+\left(-3x+7y+2\right)=$ $-\left(-3x-5y-62\right)=$ $\left(-2x-4y+82\right)-\left(-3x-5y$ $\left(-6x+5y\right)+\left(2x-4y^{+2}\right)=$ $\left(3x+8y+8\right)+\left(4x+6y=6\right)=$ $\left(a+b+c+3\right)-\left(2a-2b-2c-4\right)=$ $\left(2a-3b\right)+\left(4a+3b+5\right)=$
Bachillerato
Aritmética y álgebra
Búsquedas: 112
Solución
answer-user-profile-image
Profesor de Qanda - EliMC
answer-reply-image